Recent issues in Turkish higher education and internationalization - Atar, Cihat; Abdul Rahman, Shukran (2018)
This presentation reviews the Higher Education agenda (e.g. goals) of the Government of Turkey in order to identify the extent to which the sustainable development agenda is responded to. The study provides an account of the Higher Education system in Turkey, both strengths and weaknesses. This study also provides a case for other education contexts such as those other developing countries such as Malaysia.